Lasianthus yalaensis (Rubiaceae), a new species from peninsular Thailand - Napiroon, Tiwtawat; Poopath, Manop; Duangjai, Sutee; Balslev, Henrik; Vajrodaya, Srunya (Phytotaxa, 2018)
Lasianthus yalaensis Napiroon, Duangjai & Poopath is described and illustrated with notes on its conservation, and phylogenetic placement. The new species is morphologically similar to L. pilosus from which it differs in: its strigose branches (vs pilose), leaf blade 5–8 × 2–2.5 cm (vs 10–12.5 cm), 7–8 pairs of nerves (vs 9–15), stipules 5–7 mm long (vs <3 mm) and lanceolate (vs triangular-lanceolate), bracts 4–10 mm long (vs 4–5 mm) and covered with strigose hairs (vs pilose), flowers with cupular calyx (vs tubular), the lobes five and lanceolate (vs 5–7 and lanceolate-linear), corolla tube hirsute external surface (vs pilose) and glabrous internal surface (vs puberulous), drupes crowned by five calyx lobes (vs six), the lobes 1 mm long and strigose (vs 3 mm and pilose). Molecular analysis based on nuclear and plastid markers revealed that L. yalaensis is nested within the Asian clade and is closely related to L. pilosus.